Púrpura retiforme secundaria a rickettsia conorii - David Ferreira; João Cruz Cardoso; Lucília Pessoa; Nuno Catroze (Galicia Clínica, 2023)
Retiform purpura consists of branching purpuric lesions caused by a complete blockage of blood flow in the dermal/subcutaneous vasculature. It is an acute life-threatening disorder characterized by intravascular thrombosis and hemorrhagic infarction of the skin complicated with disseminated intravascular coagulation. It is commonly seen in acute infections following meningococcal and streptococcal infections. Few cases have been described of retiform purpura following rickettsial infections in the literature and rarely with this magnitude. The purpose of this report is to highlight the possibility of this situation in critically ill patients. We report a case of a 62-year-old woman admitted in the intensive care unit with septic shock from Rickettsia conorii. She developed quickly an intense retiform purpura requiring several surgical interventions to control the necrosis. The dermatologic situation was only completely controlled with treatment of underlying situation. This is a severe complication of a critical infectious disease.